Impact of Clinical and Therapeutic Factors on Incident Cardiovascular and Cerebrovascular Events in a Population‐Based Cohort of HIV‐Infected and Non–HIV‐Infected Adults. Issue 9 (September 2014) - Tripathi, Avnish; Liese, Angela D.; Winniford, Michael D.; Jerrell, Jeanette M.; Albrecht, Helmut; Rizvi, Ali A.; Zhang, Jiajia; Duffus, Wayne A.
Abstract Background Cardiovascular and cerebrovascular (CVD) events/diseases are a common cause of non–acquired immunodeficiency syndrome (AIDS)‐related mortality in the aging human immunodeficiency virus (HIV)‐infected population. The incidence rate and clinical correlates of CVD in people living with HIV/AIDS compared to the general population warrants further investigation. Hypothesis HIV/AIDS is associated with increased risk CVD compared to general population. Methods CVD events in a matched cohort of HIV‐infected and non–HIV‐infected adults, ≥18 years old, served through the South Carolina Medicaid program during 1994 to 2011 were examined using time‐dependent proportional hazards regression and marginal structural modeling. Results A retrospective cohort of 13 632 adults was followed longitudinally for an average of 51 months. The adjusted hazard ratio (aHR) of incident CVD events was higher among HIV‐infected individuals exposed to combination antiretroviral therapy (cART) (aHR = 1.15) compared to the non–HIV‐infected group, but did not differ from the subgroup of cART‐naïve HIV‐infected adults. A higher aHR of incident CVD was associated with comorbid hypertension (aHR = 2.18), diabetes (aHR = 1.38), obesity (aHR = 1.30), tobacco use (aHR = 1.47), and hepatitis C coinfection (aHR = 1.32), and older age (aHR = 1.26), but with a lower risk among females (aHR = 0.86). A higher risk of incident CVD events was also apparent in HIV‐infected individuals with exposure to both protease inhibitors (adjusted risk ratio [aRR] = 1.99) and non‐nucleoside reverse transcriptase inhibitors (aRR = 2.19) compared to those with no exposure. Sustained viral load suppression was associated with a lower risk of incident CVD events (aRR = 0.74). Conclusions After adjusting for traditional risk factors and sociodemographic differences, there is higher risk of incident cardiovascular events among HIV‐infected individuals exposed to combined antiretroviral medications compared to the general population.